Boosting in British Columbia: The Creation and Rise of Invermere - Meredith, Thomas (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1988)
Boosting has been shown to have been significant in determining urban landscapes in Canada, particularly in relatively homogeneous regions where the environment provides little local comparative advantage. The mountainous southeast of British Columbia is an area where stark physiographic contrasts suggest that the potential for effective boosterism might be small.In 1904 Randolf Bruce — a young Scottish surveyor and mine owner — became land agent for CPR holdings around Lake Windermere. Bruce, the CPR establishment, and eventually a company called the Columbia Valley Irrigated Fruit lands Company (CVIF) were dominant forces in local development. The advantages of controlling the regional urban centre were sufficiently evident that in 1911 Bruce, through the CVIF, created the Village of Invermere. Oral history, company records and contemporary journalism demonstrate that the booster ethic was present. It is a testimony to the role of this force that despite locational disadvantages, Invermere became, and remains to this day, the dominant community of the region.